Complete State Trials of the Tudor Era - Taylor, James D. (Algora Publishing, 2019)
This book presents the documentation of all known recorded capital trials within the Tudor dynasty, each encapsulating the drama and intrigue of real history as Tudor law evolved from following the monarch's will to following clearly-established law. While capital punishment was common, several individuals accused of treason skillfully and successfully defended themselves.